2019
DOI: 10.3390/en12214047
|View full text |Cite
|
Sign up to set email alerts
|

Model Verification and Justification Study of Spirally Corrugated Pipes in a Ground-Air Heat Exchanger Application

Abstract: Ground-air heat exchangers have become an important topic in recent years due to their contributions to the market growth of the ground source heat pump industry. This paper provides a comprehensive study and recommends suggestions on the selection process of a suitable pipe for an air-to-water heat pump (AWHP). Parametric studies including material, turbulent plate quantity, and pipe type were performed to identify an optimal pipe design for high-performance AWHP. Both numerical and experimental studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Lee et al studied ground air heat exchanger with a spirally corrugated plate. The study results indicated inlet-outlet temperature and pressure difference, respectively, of 4.02 °C and 14.43 Pa for 0 plates, 4.21 °C and 248.6 Pa for four plates, 5.28 °C and 469.23 Pa for six plates, and 5.81 °C and 723.02 Pa for eight plates (Lee et al, 2019). Liu et al studied the feasibility and performance of ground source heat pump under three different climate cities in China with TRNSYS simulation.…”
Section: Introductionmentioning
confidence: 92%
“…Lee et al studied ground air heat exchanger with a spirally corrugated plate. The study results indicated inlet-outlet temperature and pressure difference, respectively, of 4.02 °C and 14.43 Pa for 0 plates, 4.21 °C and 248.6 Pa for four plates, 5.28 °C and 469.23 Pa for six plates, and 5.81 °C and 723.02 Pa for eight plates (Lee et al, 2019). Liu et al studied the feasibility and performance of ground source heat pump under three different climate cities in China with TRNSYS simulation.…”
Section: Introductionmentioning
confidence: 92%
“…The impact of using different materials such as PVC, stainless steel, and copper, for the construction of an EAHE has been studied (Bansal et al, 2010;Lee et al, 2019;Serageldin et al, 2016), and it has been concluded that the use of high conductivity materials has no significant impact over the thermal performance, due to the wall thickness of these types of pipes. Hence, it can be opted to use cheap and easy to manipulate materials for the construction of an EAHE.…”
Section: Introductionmentioning
confidence: 99%
“…According to [22][23][24], the most important factors affecting the performance of EAHE are climatic conditions and geographical location, soil type, pipe properties, burial depth and airflow rate. Therefore, many researchers investigated design and optimisation of ground exchangers using sophisticated computer tools.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers investigated design and optimisation of ground exchangers using sophisticated computer tools. In general, CFD computer tools are used when considering the impact of design aspects on the thermal operation of EAHE, heat transfer between internal air and ground [25], pressure loss [26], burial depth [27] or materials used [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation